2008
DOI: 10.1002/ejic.200701189
|View full text |Cite
|
Sign up to set email alerts
|

Steric Effects in the Self‐Assembly of Palladium Complexes with Chelating Diamine Ligands

Abstract: The influence of the steric properties of chelating diamines on the self‐assembly of [Pd(N∩N)](NO3)2 complexes with 4,4′‐bpy as bridging ligand has been studied by 1H NMR spectroscopy and X‐ray diffraction (N∩N = N,N,N′,N′‐tetramethylethylenediamine, N,N,N′,N′‐tetraethylethylenediamine, 1,3‐diaminopropane, N,N′‐dimethylpiperazine, homopiperazine and ethylenediamine). Based on crystallographic data, the steric bulk of the chelating amines in the [Pd(N∩N)]2+ cations has been characterised in two different ways. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 51 publications
4
33
0
Order By: Relevance
“…In fact, as a so metal ion Pd(II) yields stable coordination compounds with nitrogen-containing ligands (preferred over oxygen), namely, with polydentate aliphatic amines [93,95,97,[252][253][254][255][256] (Table 2). Particular care should be taken in choosing these chelating ligands, since their chemical characteristics have been shown to in�uence the stability and the selfassembly properties of the corresponding Pd(II) complexes (e.g., formation of oligomeric species) [97,257]. Actually, it has been observed that the square-planar geometry typical of Pd(II) coordination compounds is slightly distorted according to the nature of the ligands.…”
Section: Palladium For Platinum Substitution In Polyamine Complexesmentioning
confidence: 99%
“…In fact, as a so metal ion Pd(II) yields stable coordination compounds with nitrogen-containing ligands (preferred over oxygen), namely, with polydentate aliphatic amines [93,95,97,[252][253][254][255][256] (Table 2). Particular care should be taken in choosing these chelating ligands, since their chemical characteristics have been shown to in�uence the stability and the selfassembly properties of the corresponding Pd(II) complexes (e.g., formation of oligomeric species) [97,257]. Actually, it has been observed that the square-planar geometry typical of Pd(II) coordination compounds is slightly distorted according to the nature of the ligands.…”
Section: Palladium For Platinum Substitution In Polyamine Complexesmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] Among them, homometallic molecular squares, formed by the reaction of cis-protected square planar complexes with linear symmetric ditopic ligands, have been the most widely studied. [19][20][21][22][23][24][25] The assembly of metallamacrocycles containing different metal corners and/or nonsymmetric ligands using this method presents additional difficulties due to the possible generation of a mixture of isomers that are difficult to separate. To overcome this, they are generally obtained through modular self-assembly methodology.…”
mentioning
confidence: 99%
“…Deviations from the sterically predicted behavior were also reported in studies with [M(P^P)] 2+ complexes (M=Pd, Pt; P^P=dppp, dppf, and depe; dppf=bis(diphenylphosphanyl)ferrocene; depe=bis(diethylphosphanyl)ethane) 13. On the contrary, we have shown with a series of sterically characterized [Pd(N^N)] 2+ complexes that the distribution of the tectons between the [Pd(N^N)(4,4′‐bpy)] n 2 n + trimeric and tetrameric products ( n =3, 4) follows a trend concluded from crystallographic data (N^N=chelating diamine) 14…”
Section: Introductionmentioning
confidence: 70%
“…2n + trimeric and tetrameric products (n = 3, 4) follows a trend concluded from crystallographic data (N^N = chelating diamine). [14] Interested in how these steric effects are manifested, we planned and synthesized new bis(arylimino)acenaphthenes (Ar-BIANs). These compounds have been known for more than four decades, mostly involving their application in homogeneous catalysis, [15] structural and physicochemical studies, [16] and preparation and structural characterization of complexes with main-group elements.…”
Section: Introductionmentioning
confidence: 99%